Peran Teknologi dalam Membantu Anak Tunarungu Berkomunikasi - Zahra Tussyifa Izzati; Fera Ningsih Banurea; Chairani Dwi Putri; Rut Yemima; Anastasya M. Manurung; Afif Arahman; Lili Tansliova; Anggia Puteri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Children with hearing impairments face challenges in communication that can affect their social and educational development. Advances in technology have provided various innovative solutions to improve accessibility and independence of children with hearing impairments in communicating. This article discusses the role of technology in helping children with hearing impairments communicate, including hearing aids, cochlear implants, sign language interpreter applications, speech recognition technology, and digital-based learning media. With this technology, children with hearing impairments can interact more easily with their social environment, improve their communication skills, and obtain better educational opportunities.